(untitled) (Journal of Forensic Medicine & Toxicology, 2023)
Background: The future of a country depends on the status of its children. Although substantial global progress has been made in reducing child mortality, there is widespread disparities among mortality rates and causes of death in children among various geographical regions. The mortality statistics in cases of death of children due to unnatural mechanisms is of utmost importance because it directly reflects the status of a country’s development. Objective: The present study is an attempt to review the various autopsy findings to decide the cause of death with special emphasis on the unnatural mechanisms of death and explore and analyse the relation between paediatric deaths and various demographic indicators like age, sex, type of family, education status of mother and socioeconomic status of family.